Seamless lamination of a concave–convex architecture with single-layer graphene. Issue 43 (19th October 2015) - Park, Ji-Hoon; Lim, Taekyung; Baik, Jaeyoon; Seo, Keumyoung; Moon, Youngkwon; Park, Noejung; Shin, Hyun-Joon; Kyu Kwak, Sang; Ju, Sanghyun; Real Ahn, Joung
Abstract : Graphene has been used as an electrode and channel material in electronic devices because of its superior physical properties. Abstract : Graphene has been used as an electrode and channel material in electronic devices because of its superior physical properties. Recently, electronic devices have changed from a planar to a complicated three-dimensional (3D) geometry to overcome the limitations of planar devices. The evolution of electronic devices requires that graphene be adaptable to a 3D substrate. Here, we demonstrate that chemical-vapor-deposited single-layer graphene can be transferred onto a silicon dioxide substrate with a 3D geometry, such as a concave–convex architecture. A variety of silicon dioxide concave–convex architectures were uniformly and seamlessly laminated with graphene using a thermal treatment. The planar graphene was stretched to cover the concave–convex architecture, and the resulting strain on the curved graphene was spatially resolved by confocal Raman spectroscopy; molecular dynamic simulations were also conducted and supported the observations. Changes in electrical resistivity caused by the spatially varying strain induced as the graphene–silicon dioxide laminate varies dimensionally from 2D to 3D were measured by using a four-point probe. The resistivity measurements suggest that the electrical resistivity can be systematically controlled by the 3D geometry of the graphene–silicon dioxide laminate. This 3D graphene–insulator laminate will broaden the range of graphene applications beyond planar structures to 3D materials.